(untitled) (Texas Journal of Medical Science, 2022)
Teeth play an important role in the human body. Initially, human teeth were large and performed one main task - grinding food (more often, hard and coarse). But with the development of man and society, dental units began to be considered not only as devices for chewing food, but also as an aesthetic component of the appearance of successful people. The disappearance of primitive food from the diet and advances in dental science today allow anyone to have a healthy and attractive dentition. The following article is devoted to the anatomy and topography of the tooth.